The The Influence of Work Culture, Work Environment and Organizational Commitment on Employee Performance with Work Motivation as A Mediation Variable at Albarqah Medika Health Clinic - Albar, Muhammad Iqbal; Hidayat, Widi; Wihadanto, Ake (Dinasti Publisher, 2024)
This research aims to determine the influence of work culture, work environment, organizational commitment on employee performance at the Albarqah Medika health clinic. And what is the effect if mediated by work motivation variables. The research method used is quantitative research type explanatory research. The subjects in this research were 45 clinic employees. The research instrument was a direct and closed questionnaire containing questions about the research variables, as well as a study of documents available at the clinic. Data analysis in this research used SPSS 25.0 for Windows to test instruments and determine the relationship between independent variables and dependent variables without mediating variables and with mediating variables (MRA). From the research results it was found that the influence of work culture, work environment, organizational commitment and motivation work on performance with significance values respectively 0.005, 0.005, 0.010, and 0.035. And all independent variables have an influence on the dependent variable through mediating variables with significant values respectively 0.040, 0.040 and 0.005. This shows that all variable values are <0.05, meaning that Ha is accepted and Ho is rejected. The conclusion is that work culture, work environment and organizational commitment has a significant influence on performance, also when this influence is moderated by work motivation.